Expansion of human centromeric arrays in cells undergoing break-induced replication - Showman, Soyeon (My University, 2024)
Human centromeres are located within highly homogeneous mega-sized α-satellite arrays and evolve rapidly, which can lead to variation in array lengths and sequences. Proposed mechanisms for such alterations are homology directed repair mechanisms including unequal cross-over between sister chromatids, gene conversion, and break-induced replication. However, the underlying molecular mechanisms responsible for the massive, complex, and rapid sequence turn over, length variation, and homogeneous organization of centromeric arrays have not been experimentally validated. This dissertation project investigates whether centromeric array expansion and contraction can occur within limited somatic cell divisions and the molecular mechanisms responsible for this change. This thesis work has demonstrated that centromeric array length can change in somatic cells (in ~20 cell divisions) of different cell lines, with various magnitudes, in a chromosome specific manner. In addition, centromeric arrays expand more frequently than contract, which can counteract the loss of SSA of DSBs at centromeres leading to an overall increase in array length. Large contractions can occur, but usually only when the array length is significantly longer than the population average. Finally, this array length change does not occur without the BIR essential proteins RAD52 and PIF1, indicating that BIR can drive centromere sequence evolution in cells undergoing BIR. This project provided key insights into a longstanding fundamental question: how centromere sequences evolve.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: Break-induced replication; Centromere; PIF1; RAD52; Tandem repeats; α-satellite; Genetics; Molecular biology; Evolution & development; Molecular and cellular biology